Origins of Taekwondo: an ethnographic analysis of its expansion in Ecuador/Orígenes del taekwondo: un análisis etnográfico de su expansión en Ecuador - Darwin Fernando Guapi Morocho (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
Taekwondo in Ecuador has been practiced for decades, obtaining countless sport results through the years, without knowing for sure what is its birth and chronology (Ecuadorian Taekwondo Federation, 2020); so the objective of this research is to provide relevant information about its origin, development and expansion in which facts and circumstances of various actors will be described. The qualitative-descriptive method was applied through the techniques of documentary review and interview, which instrument was validated by the judgment of seven experts.  The interview was applied in the second quarter of 2020, to 15 black belt coaches with ranks above the sixth dan, granted by the WTF from different provinces of the country, about the origin of Ecuadorian taekwondo, its evolution, anecdotes and sports experiences. This work will contribute to perfect the work of future taekwondo athletes, coaches and researchers, as well as to understand the complexity of the origins and development it has had through the years, which will guarantee the acquisition of a sense of martial and sporting belonging, as well as a national identity for the participation in international competitions.